PEMEROLEHAN BAHASA ANAK TUNARUNGU - Jelyna Christine (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2016)
The objectives of this research are to find out about language acquisition of deaf children in training and observation acquisition of deaf children in training and observation. Acquisition of letters, words and sentences. This research was conducted in special school Pangudi Luhur, west Jakarta on early childhood at least 2 years old and suffered hearing impairment at the time was yet to a master a language. Where is this place for 30 years of service without using the children sign language assistance. The method used in research is case study.The Process of data collection is done by observation, interviews, and document analysis. Validity of the data carried by the extension of participation, triangulation. The result of this study show deafchildren can acquire oral language even without the help of sign language. This study found that the oral and aural approach.